Economic evaluation of reproductive and productive efficiency with creole cattle production systems in Campeche, Mexico - Torres Aburto, Víctor Fernando; Severino Lendechy, Víctor Hugo; López Reyes, Liliana Yareni; Perezgrovas Garza, Raúl Andrés; Espinosa Ortiz, Valentín Efrén; Peralta Torres, Jorge Alonso (Acta Universitaria, 2022)
The objective was to carry out an economic evaluation of reproductive and productive efficiency in production units (PU) with creole cattle from Nunkiní in Campeche, Mexico. The pregnancy rate, calving interval, birth rate, weaned calves, income, and profitability were evaluated in 10 PU. The PU showed low reproductive efficiency (pregnancy rate of 41.0% ± 1.95%), high intercalving interval (577.0 d ± 3.64 d), low birth rates (37.7% ± 2.03%), weaned calves (75.40% ± 39.30%), income of USD 1359.17 (p > 0.05), and a structure of fixed and variable costs of USD 850.57 and USD 1750.58. The sections with the greatest impact on costs were food (34.14%) and labor (30.38%), which negatively affected profitability (-48.28%). In conclusion, the evaluated PU presented low profitability because of the low reproductive and productive efficiency of the breeding stock.